Leadership For Innovation In Digital Era: A Study Of How Transformational And Transactional Leadership Styles Impact To Employee Creativity - Sentika, Sarah; Arissaputra, Rivaldi; Prianka, Winda Gafrilia; Rifai, M Syakib A; Desmantyo, Pandu Sapto (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This research delves into the critical role of leadership in stimulating employee creativity within organizations, focusing on the contrasting impacts of transactional and transformational leadership styles. Employing a quantitative approach, data was gathered through the distribution of questionnaires, with a sample size of 300 respondents. Utilizing SmartPLS for analysis, findings revealed that transactional leadership holds a stronger influence compared to transformational leadership on employee creativity. Through the validation of formulated hypotheses, it was concluded that both leadership styles significantly affect employee creativity. By combining the visionary inspiration characteristic of transformational leadership with the structured support inherent in transactional leadership, organizations can cultivate a balanced leadership ethos conducive to fostering employee creativity. Such a culture not only nurtures innovation but also enhances organizational competitiveness over the long term, positioning them for sustained growth and success in dynamic market landscapes